2019
DOI: 10.3390/ijms20164046
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 Is a Possible Promoter of Immunopathology in Rheumatoid Arthritis by Activation of Peptidyl Arginine Deiminase 4 (PAD-4) in Granulocytes

Abstract: The aetiology of rheumatoid arthritis (RA) is unknown, but citrullination of proteins is thought to be an initiating event. In addition, it is increasingly evident that the lung can be a potential site for the generation of autoimmune triggers before the development of joint disease. Here, we identified that serum levels of galectin-9 (Gal-9), a pleiotropic immunomodulatory protein, are elevated in RA patients, and are even further increased in patients with comorbid bronchiectasis, a lung disease caused by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 68 publications
(89 reference statements)
4
23
3
Order By: Relevance
“…More recently, Wiersma et al have reported that serum Gal-9 levels were elevated and correlated with disease activity (DAS-28) or smoking status in RA patient [26]. Our data are almost in line with these data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…More recently, Wiersma et al have reported that serum Gal-9 levels were elevated and correlated with disease activity (DAS-28) or smoking status in RA patient [26]. Our data are almost in line with these data.…”
Section: Discussionsupporting
confidence: 92%
“…Serum Gal-9 levels were elevated in RA patients with RA-related interstitial lung disease (RA-ILD); however, we could not find any associations between circulating Gal-9 and smoking status in our RA patients. Differences of ethnic and demographic data of the subjected RA patients may contribute to the differential result between our data and the reported data [26]. Further, large-scale investigations consisting of ethnic groups are needed to decide the mechanisms by which circulating Gal-9 is elevated in RA patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Serum Gal-9 levels were elevated in RA patients with RA-related interstitial lung disease (RA-ILD), however, we could not find any associations between circulating Gal-9 and smoking status in our RA patients. Differences of ethnics and demographic data of the subjected RA patients may contribute to the differential result between our data and the reported data [26]. Further, large-scale investigations consisting of ethnic-groups are needed to decide the mechanisms by which circulating Gal-9 is elevated in RA patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Of these 84 genes, 16 genes were NETs associated genes ( Figure 5B; Table 3) (33-46) Of the 16 genes, LGALS9, HCK, LCP1, CEACAM1 were involved in the cytokine-mediated signaling pathway. S100A8, LGALS9, and CTSC were involved in regulation of apoptotic signal by enrichment annotation from the Metascape tool ( Figure 5B; Table 3) (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Neutrophil Activation Related Genes Enrichment Analysismentioning
confidence: 99%